2015
DOI: 10.1371/journal.pone.0122251
|View full text |Cite
|
Sign up to set email alerts
|

Pik3ip1 Modulates Cardiac Hypertrophy by Inhibiting PI3K Pathway

Abstract: Cardiac hypertrophy is an adaptive response to various physiological and pathological stimuli. Phosphoinositide-3 kinase (PI3K) is a highly conserved lipid kinase involved in physiological cardiac hypertrophy (PHH). PI3K interacting protein1 (Pik3ip1) shares homology with the p85 regulatory subunit of PI3K and is known to interact with the p110 catalytic subunit of PI3K, leading to attenuation of PI3K activity in liver and immune cells. However, the role of Pik3ip1 in the heart remains unknown. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…A protein, PIK3IP1 that shares significant homology with the PI3K p85 regulatory subunit, negatively regulates PI3K. PIK3IP1 binds to the catalytic p110 subunit to prevent PI3K activation and phosphorylation of Akt in multiple cell types, including cardiac myocytes [5759, 80]. Our study provides substantial evidence for PIK3IP1 as a novel target for let-7 in the myocardium.…”
Section: Discussionmentioning
confidence: 82%
“…A protein, PIK3IP1 that shares significant homology with the PI3K p85 regulatory subunit, negatively regulates PI3K. PIK3IP1 binds to the catalytic p110 subunit to prevent PI3K activation and phosphorylation of Akt in multiple cell types, including cardiac myocytes [5759, 80]. Our study provides substantial evidence for PIK3IP1 as a novel target for let-7 in the myocardium.…”
Section: Discussionmentioning
confidence: 82%
“…By pathways enrichment analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) with the positively selected 479 genes in Abaga horse and 943 genes in Wushen horse, the enriched pathways (P≤0.05) of Abaga horse included Propanoate metabolism, Viral myocarditis, Phototransduction, PI3K-Akt signaling pathway, Glycerolipid metabolism, Morphine addiction and mRNA surveillance pathway in which the pathway with the largest number of enriched genes (13 genes) was PI3K-Akt signaling pathway. As intracellular basal signaling pathways, PI3K-Akt signaling pathway involves lots of vital movement, such as exercise-induced physiologic hypertrophy (Shioi et al 2002; Luo et al 2005; Sagara et al 2012; Song et al 2015) and protecting mitochondria of skeletal muscle by aerobic endurance training (Liu et al 2016), further explaining the excellent athletic performance of Abaga horse. Besides that, the enriched pathways (P≤0.05) of Wushen horse contained Base excision repair, Glutamatergic synapse, Endometrial cancer, Glycolysis / Gluconeogenesis, Propanoate metabolism and ABC transporters (Figure 6A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Further on SNPs, we analyzed functions of 440 genes of Abaga horse without 39 overlapped genes of positively selected genes between Abaga horse and Wushen horse. We focused on the enriched exercise-related pathways which referred to Metabolic pathways (Hill et al 2010), Ras signaling pathway (Shioi et al 2002; Xie et al 2007), PI3K-Akt signaling pathway (Shioi et al 2002; Luo et al 2005; Sagara et al 2012; Standard et al 2014; Song et al 2015; Liu et al 2016; Vega et al 2017), MAPK signaling pathway (Schröder et al 2011), Hippo signaling pathway (Gabriel et al 2016), Valine, leucine and isoleucine degradation (McGivney et al 2010), Cardiac muscle contraction (Do et al 2015), NF-kappa B signaling pathway (Kramer and Goodyear 2007), Arachidonic acid metabolism (Hill et al 2010), Regulation of actin cytoskeleton (Hill et al 2010; Schröder et al 2011), Insulin signaling pathway (Gim et al 2004; Hill et al 2010) and Fatty acid metabolism (Gim et al 2004; Hill et al 2010) in the 440 positively selected genes of Abaga horse that distinguished from Wushen horse (Figure 7). These enriched pathways comprised some recurrent genes (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…17 PI3K generates phospholipids known to regulate Akt activity in promoting cardiac hypertrophy. 18 Our previous study reported that Akt-1 protein level significantly increased in the fetal hearts with GC. 19 In this study, we investigated whether antenatal GC affects the downstream mechanisms of Akt-1 underlying the development of cardiac hypertrophy in fetal rats.…”
mentioning
confidence: 90%
“…reported that phosphatidylinositol‐3 kinase (PI3K) is essential for the induction of physiological cardiac hypertrophy . PI3K generates phospholipids known to regulate Akt activity in promoting cardiac hypertrophy . Our previous study reported that Akt‐1 protein level significantly increased in the fetal hearts with GC…”
mentioning
confidence: 99%